2015
DOI: 10.4081/ijfs.2015.4515
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Listeria innocua contamination in vacuum-packaged dry-cured Italian pork products after high hydrostatic pressure treatment

Abstract: The present work aims to present the results of the application of a treatment with high hydrostatic pressure (HHP) on Italian fermented and dry-cured pork products. The products used in this study were portioned cured ham, portioned bacon and salami, vacuumpackaged and produced by a single processing company. Two studies were conducted on a single batch of the three products by means of an artificial contamination with Listeria innocua as a surrogate of L. monocytogenes. In the first trial a superficial conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Various authors have tested the inactivation of L. monocytogenes in other unfermented meat products by HPP (Garriga et al, 2004;Hugas et al, 2002;Merialdi et al, 2015), many of them in dry-cured ham (Morales et al, 2006;Bover-Cid et al, 2011;Hereu et al, 2012;Bover-Cid et al, 2015): Hereu et al (2012) have reported a reduction of L. monocytogenes from 1.82 to 3.85 log CFU/g in artificially contaminated sliced ham after treatment at 600 MPa for 5 min, Bover-Cid et al (2011), through a HPP treatment at 613 MPa for 5 min., achieved the 2.39D proposed by Hoz et al (2008) to meet the USA zero tolerance policy, Bover-Cid et al (2015) showed a reduction of L. monocytogenes in dry-cured ham at 600MPa for 5 minutes ranging from 2.24 log to 6.82 Log CFU/g depending on the a w and fat content of the ham.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various authors have tested the inactivation of L. monocytogenes in other unfermented meat products by HPP (Garriga et al, 2004;Hugas et al, 2002;Merialdi et al, 2015), many of them in dry-cured ham (Morales et al, 2006;Bover-Cid et al, 2011;Hereu et al, 2012;Bover-Cid et al, 2015): Hereu et al (2012) have reported a reduction of L. monocytogenes from 1.82 to 3.85 log CFU/g in artificially contaminated sliced ham after treatment at 600 MPa for 5 min, Bover-Cid et al (2011), through a HPP treatment at 613 MPa for 5 min., achieved the 2.39D proposed by Hoz et al (2008) to meet the USA zero tolerance policy, Bover-Cid et al (2015) showed a reduction of L. monocytogenes in dry-cured ham at 600MPa for 5 minutes ranging from 2.24 log to 6.82 Log CFU/g depending on the a w and fat content of the ham.…”
Section: Discussionmentioning
confidence: 99%
“…The L. innocua inoculum culture was prepared using a mixture of 5 strains: IZSLER 111373/1 and IZSLER 111373/2 isolated from industrial site (superficial swab collected in pork meat transformation plant), IZSLER 257529/1 isolated from fresh pork sausages, IZSLER 257529/2 isolates from fresh swine meat and the reference strain ATCC 33090, 100 µL of a stock culture (stored in 20% glycerol at -80°C) of each strain were transferred to 10 ml Brain Heart Infusion (BHI) broth and incubated for 24 h at 30°C. Subsequently, an aliquot of 100 µl was transferred to 1000 mL BHI broth and incubated at 12°C for 72 h (Merialdi et al, 2015).…”
Section: Inoculum Compositionmentioning
confidence: 99%
See 1 more Smart Citation